The slope-intercept form is <math><mstyle displaystyle="true"><mi>y</mi><mo>=</mo><mi>m</mi><mi>x</mi><mo>+</mo><mi>b</mi></mstyle></math> , where <math><mstyle displaystyle="true"><mi>m</mi></mstyle></math> is the slope and <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> is the y-intercept.

Find the values of <math><mstyle displaystyle="true"><mi>m</mi></mstyle></math> and <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> using the form <math><mstyle displaystyle="true"><mi>y</mi><mo>=</mo><mi>m</mi><mi>x</mi><mo>+</mo><mi>b</mi></mstyle></math> .

The slope of the line is the value of <math><mstyle displaystyle="true"><mi>m</mi></mstyle></math> , and the y-intercept is the value of <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> .

Slope: <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math>

y-intercept: <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mn>14</mn><mo>)</mo></mrow></mstyle></math>

Slope: <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math>

y-intercept: <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mn>14</mn><mo>)</mo></mrow></mstyle></math>

Find the x-intercept.

To find the x-intercept(s), substitute in <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> for <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> and solve for <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> .

Solve the equation.

Rewrite the equation as <math><mstyle displaystyle="true"><mn>6</mn><mi>x</mi><mo>+</mo><mn>14</mn><mo>=</mo><mn>0</mn></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>14</mn></mstyle></math> from both sides of the equation.

Divide each term by <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> and simplify.

Divide each term in <math><mstyle displaystyle="true"><mn>6</mn><mi>x</mi><mo>=</mo><mo>-</mo><mn>14</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Simplify <math><mstyle displaystyle="true"><mfrac><mrow><mo>-</mo><mn>14</mn></mrow><mrow><mn>6</mn></mrow></mfrac></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mo>-</mo><mn>14</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mo>-</mo><mn>14</mn></mstyle></math> .

Cancel the common factors.

Factor <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Move the negative in front of the fraction.

x-intercept(s) in point form.

x-intercept(s): <math><mstyle displaystyle="true"><mrow><mo>(</mo><mo>-</mo><mfrac><mrow><mn>7</mn></mrow><mrow><mn>3</mn></mrow></mfrac><mo>,</mo><mn>0</mn><mo>)</mo></mrow></mstyle></math>

x-intercept(s): <math><mstyle displaystyle="true"><mrow><mo>(</mo><mo>-</mo><mfrac><mrow><mn>7</mn></mrow><mrow><mn>3</mn></mrow></mfrac><mo>,</mo><mn>0</mn><mo>)</mo></mrow></mstyle></math>

Find the y-intercept.

To find the y-intercept(s), substitute in <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> for <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> and solve for <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> .

Solve the equation.

Remove parentheses.

Simplify <math><mstyle displaystyle="true"><mn>6</mn><mrow><mo>(</mo><mn>0</mn><mo>)</mo></mrow><mo>+</mo><mn>14</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> .

Add <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>14</mn></mstyle></math> .

y-intercept(s) in point form.

y-intercept(s): <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mn>14</mn><mo>)</mo></mrow></mstyle></math>

y-intercept(s): <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mn>14</mn><mo>)</mo></mrow></mstyle></math>

Create a table of the <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> and <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> values.

Graph the line using the slope and the y-intercept, or the points.

Slope: <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math>

y-intercept: <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mn>14</mn><mo>)</mo></mrow></mstyle></math>

Do you know how to Graph 8x-2(x-7)? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.